Eficacia del albendazol y rafoxanida contra Fasciola hepatica en vacunos procedentes del norte del Perú - Zárate-Rendón, Daniel (2024)
The aim of this study was to determine the effectiveness of a combination of albendazole and rafoxanide against Fasciola hepatica in cattle from the northern region of Lambayeque fattened in an intensive fattening centre in Lima, Peru. Twenty-one naturally infected bulls treated with a combination of albendazole (9 mg/kg) and rafoxanide (10 mg/kg) (Ranide Forte®, TQC, Peru) were used. The effectiveness of the drug was determined using the faecal egg count reduction test (FECRT) with faecal samples collected on days 14 and 30 of dosing. The number of eggs per gram of faeces (epg) was determined with the FLUKEFINDER® method. The bootstrapping method in the R program was used to generate the 95% confidence intervals. The efficacy of the compound was 94% (90:98 95% CI) on day 14 and 100% on day 30. It is shown that rafoxanide in combination with albendazole is a good therapeutic option against fasciolosis in cattle from the northern Peru.